MODERN RECOMMENDATIONS ON BASIC CARDIOPULMONARY RESUSCITATION FOR CHILDREN - R.F. Tepaev (Union of pediatricians of Russia, 2010)
The major causes of death in children and adolescents in Russia are the external reasons, such as traumas, poisonings, drowning and transport incidents. Many injuries are preventable. Popularization of up to date methods of basic life support is one of methods of declining of a mortality of victims of out-of-hospital arrest. This article highlights the American Heart Association Guidelines for Pediatric Basic Life Support. Key words: basic life support, children, adolescents. (Pediatric Pharmacology. - 2010; 7(4):24-29)